Free radical-thermal cation dual-curing tempered film coating, free radical-thermal cation dual-curing tempered film and preparation method of free radical-thermal cation dual-curing tempered film

By using free radical-thermal cation dual curing technology in the tempered film, the cross-linking network structure of epoxy acrylic oligomer and polyurethane acrylate is constructed, which solves the problems of poor impact resistance and complex production of the existing tempered film, and achieves the effects of high-efficiency energy absorption, wear resistance, high light transmittance and uniform film thickness.

CN119684890AInactive Publication Date: 2025-03-25GUANGZHOU TETRAHEDRON NEW MATERIAL TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411953688.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing fiberglass tempered films are poorly impact-resistant and fragile, and have high production costs; the production process of single UV cured PET tempered films is complex and difficult to control, and double-sided coating is required to avoid high hard surface curl of the film.

Method used

The free radical-thermal cation dual curing tempered film coating is used to construct a cross-linking network structure through epoxy acrylic oligomer and polyurethane acrylate, and combine a composite photoinitiator and a thermal cation initiator to achieve rapid dual curing and deep cross-linking.

Benefits of technology

It achieves high-efficiency energy absorption and dispersion capabilities, provides impact resistance at a height of 150cm, improves wear resistance, maintains light transmittance above 92%, and significantly improves film thickness uniformity and user experience.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005215414930000081
    Figure BDA0005215414930000081
  • Figure BDA0005215414930000091
    Figure BDA0005215414930000091
Patent Text Reader

Abstract

The invention discloses a free radical-thermal cation dual-curing tempered film coating, a free radical-thermal cation dual-curing tempered film and a preparation method of the free radical-thermal cation dual-curing tempered film, and relates to the field of dual-curing materials. The invention relates to a photoinitiator, which is prepared from the following components in parts by weight: 0.5 to 1.5 parts of epoxy acrylate oligomer, 2 to 4 parts of polyurethane acrylate, 3 to 6 parts of solvent, compound photoinitiator accounting for 2 to 4 percent of the total weight of the component, thermal cationic initiator accounting for 0.5 to 3 percent of the total weight of the component, and assistant accounting for 0.1 to 0.5 percent of the total weight of the component. By optimizing the ratio of the urethane acrylate to the epoxy acrylate oligomer, excellent film material smoothness is realized under the condition of single-sided coating, and the curl phenomenon of a high-hardness surface is eliminated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of dual-cured materials, in particular to a free radical-thermal cation dual-cured tempered film coating, a free radical-thermal cation dual-cured tempered film and a preparation method thereof. Background Art

[0002] With the popularity of smart phones and the increasing demand for mobile phone protection, tempered films have gradually become a necessity in people's lives. Initially, mobile phone screen protection mainly relied on ordinary plastic films, but their protective effect was limited and they were easily scratched and worn. With the advancement of technology, tempered films came into being and quickly occupied the market with their powerful protective performance. However, glass tempered films have disadvantages such as poor impact resistance, fragility, and high production costs; single UV-cured PET tempered films require double-sided coating to prevent the film from curling toward the high hard surface, and the production process is complicated and difficult to control. Therefore, it is necessary to provide a technical solution to solve the above problems. Summary of the invention

[0003] The purpose of this application is to provide a technical solution to solve the problems raised in the above background technology.

[0004] To achieve the above objectives, this application provides the following technical solutions:

[0005] A free radical-thermal cationic dual-curing toughened film coating, comprising, by weight:

[0006] 0.5-1.5 parts of epoxy acrylate oligomer, 2-4 parts of polyurethane acrylate, 3-6 parts of solvent, 2%-4% of composite photoinitiator accounting for the total weight of the mixture, 0.5%-3% of thermal cationic initiator accounting for the total weight of the mixture, and 1‰-5‰ of auxiliary agent accounting for the total weight of the mixture.

[0007] Preferably, the composite photoinitiator comprises 1-hydroxycyclohexyl phenyl ketone and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, and the ratio of the 1-hydroxycyclohexyl phenyl ketone to the 2,4,6-trimethylbenzoyl-diphenylphosphine oxide is 2:1.

[0008] Preferably, the thermal cationic initiator is diphenyl[4-(phenylthio)phenyl]-sulfonium hexafluoroantimonate.

[0009] Preferably, the solvent includes butyl acetate, methyl isobutyl ketone and propylene glycol monomethyl ether, and the ratio of the butyl acetate, the methyl isobutyl ketone and the propylene glycol monomethyl ether is 5:3:2.

[0010] Preferably, the auxiliary agent is one or more of a leveling agent and a catalyst.

[0011] A method for preparing a free radical-thermal cationic dual-curing toughened film coating comprises the following steps:

[0012] (1) Add 0.5-1.5 parts of epoxy acrylate oligomer, 2-4 parts of polyurethane acrylate and 3-6 parts of solvent into a beaker and stir evenly at room temperature;

[0013] (2) Then add 2% to 4% of composite initiator, 0.5% to 3% of thermal cationic initiator, and 1‰ to 5‰ of auxiliary agent, and continue to stir evenly;

[0014] (3) Vacuum degassing and discharging.

[0015] A method for preparing a free radical-thermal cationic dual-curing tempered film comprises the following steps:

[0016] (1) preparing a substrate, uniformly coating a free radical-thermal cationic dual-cured tempered film coating obtained from claim 6 on the surface of the substrate, and baking the coating in an oven at a temperature above 110° C. for 2 min to 4 min;

[0017] (2) The baked substrate is passed through a high pressure mercury lamp at 600-800 mj / cm 2 Energy curing until the coating is dry; curing time is 1s-5s;

[0018] (3) The cured substrate is placed in an oven at 60°C-80°C for 24h-48h to complete the preparation.

[0019] A free radical-thermal cation dual-cured tempered film is prepared based on the above-mentioned free radical-thermal cation dual-cured tempered film preparation method.

[0020] Preferably, the substrate is PET.

[0021] Preferably, the epoxy acrylic oligomer is selected from one or more of Changxing 6270, Changxing 6278, Daicel CELLOXIDE 2000, and Daicel EPOLEAD PB3600.

[0022] In summary, the technical effects and advantages of the present invention are as follows:

[0023] 1. The present invention introduces epoxy acrylic oligomers and polyurethane acrylates to construct a cross-linked network structure with both flexibility and strength, giving the coating efficient energy absorption and dispersion capabilities. According to the steel ball free fall test, the coating can withstand a 150cm height impact, and the breakage rate is significantly reduced, which is suitable for smart devices with high impact resistance requirements.

[0024] 2. The present invention adopts a composite photoinitiator (1-hydroxycyclohexyl phenyl ketone and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide) to improve the crosslinking density and make the coating hardness reach 9H. At the same time, combined with the surface strengthening effect of polyurethane acrylate, the wear resistance is improved. It can withstand 3500 frictions under 500g pressure without obvious wear, thereby extending the service life of the product.

[0025] 3. The present invention optimizes the ratio of polyurethane acrylate to epoxy acrylate oligomer, achieves excellent film flatness in the case of single-sided coating, and eliminates the curling phenomenon of high hard surface of polyurethane acrylate free radical polymerization. Epoxy acrylate oligomer and thermal cationic initiator (diphenyl [4- (phenylthio) phenyl] - hexafluoroantimonate sulfonium) are introduced, and the thermal cationic initiator is decomposed at above 110 ° C to release protons to initiate the ring-opening polymerization reaction of epoxy acrylate oligomer, forming a deep cross-linked network, effectively reducing the curing shrinkage to less than 2%, significantly reducing internal stress and solving the curling phenomenon, and then combined with UV curing to achieve rapid dual curing, significantly shortening the process time and improving production efficiency.

[0026] 4. The present invention selects highly transparent epoxy acrylic oligomers and combines them with composite photoinitiators to ensure that the light transmittance of the coating is stable at more than 92%, and there is no yellowing during the curing process, thereby maintaining the high definition and color reproduction of the screen.

[0027] 5. This solution introduces a leveling agent into the coating and combines it with a dense cross-linked structure to form a super hydrophobic surface with a hydrophobic angle of 110°. It not only effectively prevents oil stains from adhering, but also facilitates daily cleaning, significantly improving the user experience.

[0028] 6. The present invention controls the coating curing process through the dual curing mechanism of thermal cation and UV, so that the film thickness deviation is controlled within ±0.5um, the coating uniformity is greatly improved, and the consistency of each batch of products is ensured. DETAILED DESCRIPTION

[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0030] Embodiment 1:

[0031] (1) Add 0.5 parts of epoxy acrylate oligomer (Changxing 6270), 2 parts of polyurethane acrylate and 3 parts of solvent (butyl acetate: methyl isobutyl ketone: propylene glycol monomethyl ether = 5:3:2) into a beaker and stir evenly at room temperature for 10 minutes;

[0032] (2) Add 2% composite photoinitiator (1-hydroxycyclohexyl phenyl ketone and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide in a ratio of 2:1), 0.5% thermal cationic initiator (diphenyl [4- (phenylthio) phenyl] - hexafluoroantimonate sulfonium) and 1‰ fluorosilicone leveling agent, and continue stirring for 15 minutes;

[0033] (3) vacuum degassing the mixture for 10 minutes to ensure that the bubbles are completely eliminated;

[0034] (4) coating the coating liquid on the surface of the PET substrate, and the coating thickness is controlled to be 10 μm;

[0035] (5) placing the coated substrate in an oven at 115°C for 3 minutes;

[0036] (6) Use high pressure mercury lamp 600mj / cm 2 Energy irradiation curing for 2 seconds until the coating surface is dry:

[0037] (7) Finally, the cured substrate was placed in a 70° C. oven for aging for 24 hours to obtain a free radical-thermal cationic dual-cured tempered film.

[0038] Embodiment 2:

[0039] (1) Add 1 part of epoxy acrylate oligomer (Changxing 6278), 3 parts of polyurethane acrylate and 4 parts of solvent (butyl acetate: methyl isobutyl ketone: propylene glycol monomethyl ether = 5:3:2) into a beaker and stir at room temperature for 15 minutes until the mixture is uniform;

[0040] (2) Add 3% composite photoinitiator (1-hydroxycyclohexyl phenyl ketone and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide in a ratio of 1:2), 1% thermal cationic initiator (diphenyl [4- (phenylthio) phenyl] - hexafluoroantimonate sulfonium) and 2‰ catalyst, and continue stirring for 10 minutes to ensure complete uniformity;

[0041] (3) vacuum degassing for 10 minutes until the mixture is uniform and free of bubbles;

[0042] (4) coating the coating liquid on the surface of the PET substrate, and the coating thickness is controlled to be 8 μm;

[0043] (5) placing the coated substrate in an oven at 120° C. and baking for 4 minutes;

[0044] (6) Use high pressure mercury lamp 800mj / cm 2 Energy curing for 3 seconds until the coating is dry:

[0045] (7) Finally, the substrate was placed in an oven at 70°C for 36 hours to obtain a free radical-thermal cationic dual-cured tempered film.

[0046] Embodiment 3:

[0047] (1) Add 0.8 parts of epoxy acrylate oligomer (Daicel CELLOXIDE 2000), 3.5 parts of polyurethane acrylate and 5 parts of solvent (butyl acetate: methyl isobutyl ketone: propylene glycol monomethyl ether = 5:3:2) into a beaker and stir evenly for 10 minutes;

[0048] (2) adding 3.5% composite photoinitiator, 1.5% thermal cationic initiator (diphenyl[4-(phenylthio)phenyl]-hexafluoroantimonate sulfonium) and 3‰ fluorosilicone leveling agent and catalyst mixing aid, stirring for 15 minutes until the mixture is uniform;

[0049] (3) performing vacuum degassing for 10 minutes to obtain a uniform, bubble-free coating liquid;

[0050] (4) coating the coating liquid on the surface of the PET substrate with a thickness controlled to be 12 μm;

[0051] (5) placing the coated substrate in an oven at 110° C. for 2 minutes;

[0052] (6) Use high pressure mercury lamp 600mj / cm 2 Energy cure for 4 seconds to ensure complete cure:

[0053] (7) Finally, the cured substrate was placed in an oven at 60° C. for 48 hours to obtain a free radical-thermal cationic dual-cured tempered film.

[0054] Embodiment 4:

[0055] (1) Mix 1.2 parts of epoxy acrylate oligomer (Changxing 6278 and Daicel CELLOXIDE 2000 in a ratio of 1:1), 2.5 parts of polyurethane acrylate and 3 parts of solvent (same ratio as above) in a beaker and stir evenly for 15 minutes;

[0056] (2) Mix 1.2 parts of epoxy acrylate oligomer (Changxing 6278 and Daicel CELLOXIDE 2000 in a ratio of 1:1), 2.5 parts of polyurethane acrylate and 3 parts of solvent (same ratio as above) in a beaker and stir evenly for 15 minutes;

[0057] (3) Vacuum degassing the mixture for 10 minutes to ensure that there are no bubbles;

[0058] (4) coating the coating liquid on the surface of the PET substrate with a thickness controlled to be 10 μm;

[0059] (5) placing the coated substrate in an oven at 115°C for 3 minutes;

[0060] (6) Use high pressure mercury lamp 600mj / cm2 Energy irradiation curing for 3 seconds until the coating surface is dry:

[0061] (7) Finally, the cured substrate was placed in an oven at 75° C. for 36 hours to obtain a free radical-thermal cationic dual-cured tempered film.

[0062] Embodiment 5:

[0063] (1) Add 1 part of epoxy acrylate oligomer (Changxing 6270), 4 parts of polyurethane acrylate and 6 parts of solvent (butyl acetate: methyl isobutyl ketone: propylene glycol monomethyl ether = 5:3:2) into a beaker and stir evenly for 10 minutes;

[0064] (2) Add 3.2% composite photoinitiator, 2% thermal cationic initiator and 5‰ fluorosilicone leveling agent, and continue stirring for 15 minutes;

[0065] (3) vacuum degassing the mixture for 10 minutes to ensure that the bubbles are completely eliminated;

[0066] (4) coating the coating liquid on the surface of the PET substrate, and the coating thickness is controlled to be 15 μm;

[0067] (5) placing the coated substrate in an oven at 115°C for 3 minutes;

[0068] (6) Use high pressure mercury lamp 600mj / cm 2 Energy irradiation curing for 2 seconds until the coating surface is dry:

[0069] (7) Finally, the cured substrate was placed in a 70° C. oven for aging for 48 hours to obtain a free radical-thermal cationic dual-cured tempered film.

[0070] Embodiment 6:

[0071] (1) Add 0.7 parts of epoxy acrylate oligomer (Daicel EPOLEAD PB3600), 2.5 parts of polyurethane acrylate and 4 parts of solvent (butyl acetate: methyl isobutyl ketone: propylene glycol monomethyl ether = 5:3:2) into a beaker and stir evenly for 15 minutes;

[0072] (2) Add 2.5% composite photoinitiator (1-hydroxycyclohexyl phenyl ketone and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide in a ratio of 3:1), 1.2% thermal cationic initiator (diphenyl [4-(phenylthio) phenyl]-hexafluoroantimonate sulfonium) and 3‰ fluorosilicone leveling agent, and continue stirring for 10 minutes until completely uniform;

[0073] (3) Perform vacuum degassing for 10 minutes to ensure that the bubbles are completely removed;

[0074] (4) coating the coating liquid on the surface of the PET substrate with a thickness controlled to be 10 μm;

[0075] (5) placing the coated substrate in an oven at 110° C. for 3 minutes;

[0076] (6) Using high pressure mercury lamp 650mj / cm 2 Energy irradiation cure for 4 seconds until the coating is completely dry:

[0077] (7) Finally, the cured substrate was placed in a 60° C. oven for aging for 48 hours to obtain a free radical-thermal cationic dual-cured tempered film.

[0078] Embodiment 7:

[0079] (1) Add 1.4 parts of epoxy acrylate oligomer (Changxing 6278), 3.5 parts of polyurethane acrylate and 4.5 parts of solvent (butyl acetate: methyl isobutyl ketone: propylene glycol monomethyl ether = 4:3:3) into a beaker and stir evenly for 10 minutes;

[0080] (2) Add 3% composite photoinitiator (1-hydroxycyclohexyl phenyl ketone and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide in a ratio of 2:1), 1.5% thermal cationic initiator (diphenyl [4- (phenylthio) phenyl] - hexafluoroantimonate sulfonium) and 5‰ catalyst, and stir evenly for 15 minutes;

[0081] (3) Perform vacuum degassing for 10 minutes to ensure uniformity and absence of bubbles;

[0082] (4) coating the coating liquid on the surface of the PET substrate with a thickness controlled to be 12 μm;

[0083] (5) placing the coated substrate in an oven at 115°C for 2 minutes;

[0084] (6) Use high pressure mercury lamp 800mj / cm 2 Energy irradiation curing for 3 seconds until the coating surface is dry:

[0085] (7) Finally, the cured substrate was placed in a 75°C oven for aging for 36 hours to obtain a free radical-thermal cationic dual-cured tempered film.

[0086] Embodiment 8:

[0087] (1) Add 1 part of epoxy acrylate oligomer (Changxing 6270 and Daicel CELLOXIDE 2000 mixed in a ratio of 1:1), 2.8 parts of polyurethane acrylate and 4 parts of solvent (butyl acetate: methyl isobutyl ketone: propylene glycol monomethyl ether = 6:2:2) into a beaker and stir evenly for 15 minutes;

[0088] (2) adding 2.8% composite photoinitiator, 1% thermal cationic initiator (diphenyl[4-(phenylthio)phenyl]-hexafluoroantimonate sulfonium) and 4‰ fluorosilicone leveling agent to the catalyst mixture, stirring for 10 minutes until the mixture is uniform;

[0089] (3) Perform vacuum degassing for 10 minutes to ensure that the mixed solution is free of bubbles;

[0090] (4) coating the coating liquid on the surface of the PET substrate, and the coating thickness is controlled to be 10 μm;

[0091] (5) placing the coated substrate in an oven at 120° C. for 4 minutes;

[0092] (6) Use high pressure mercury lamp 750mj / cm 2 Energy irradiation curing for 3 seconds until the coating surface is dry:

[0093] (7) Finally, the cured substrate was placed in a 70° C. oven for aging for 24 hours to obtain a free radical-thermal cationic dual-cured tempered film.

[0094] Embodiment 9:

[0095] (1) Add 0.9 parts of epoxy acrylate oligomer (Daicel EPOLEAD PB3600), 3.2 parts of polyurethane acrylate and 5.2 parts of solvent (butyl acetate: methyl isobutyl ketone: propylene glycol monomethyl ether = 5:3:2) into a beaker and stir evenly for 10 minutes;

[0096] (2) adding 3.7% composite photoinitiator, 1.8% thermal cationic initiator (diphenyl[4-(phenylthio)phenyl]-hexafluoroantimonate sulfonium) and 3‰ catalyst, and stirring evenly for 15 minutes;

[0097] (3) vacuum degassing the mixture for 10 minutes to ensure that the bubbles are completely eliminated;

[0098] (4) coating the coating liquid on the surface of the PET substrate, and the coating thickness is controlled to be 15 μm;

[0099] (5) placing the coated substrate in an oven at 110° C. for 3 minutes;

[0100] (6) Use high pressure mercury lamp 700mj / cm 2 Energy irradiation curing for 2 seconds until the coating surface is dry:

[0101] (7) Finally, the cured substrate was placed in a 70° C. oven for aging for 48 hours to obtain a free radical-thermal cationic dual-cured tempered film.

[0102] Embodiment 10:

[0103] (1) Add 1 part of epoxy acrylate oligomer (Changxing 6278), 3.8 parts of polyurethane acrylate and 6 parts of solvent (butyl acetate: methyl isobutyl ketone: propylene glycol monomethyl ether = 5:3:2) into a beaker and stir evenly for 10 minutes;

[0104] (2) Add 3.5% composite photoinitiator, 2.2% thermal cationic initiator (diphenyl [4- (phenylthio) phenyl] - hexafluoroantimonate sulfonium) and 5‰ fluorosilicone leveling agent, and stir evenly for 15 minutes until completely uniform;

[0105] (3) vacuum degassing the mixture for 10 minutes to remove residual bubbles;

[0106] (4) coating the coating liquid on the surface of the PET substrate, and the coating thickness is controlled to be 8 μm;

[0107] (5) placing the coated substrate in an oven at 120° C. for 4 minutes;

[0108] (6) Using high pressure mercury lamp 850mj / cm 2 Energy irradiation curing for 4 seconds until the coating surface is dry:

[0109] (7) Finally, the cured substrate was placed in a 75°C oven for aging for 36 hours to obtain a free radical-thermal cationic dual-cured tempered film.

[0110] This solution uses UV photoinitiators to quickly generate free radicals, triggering the chain polymerization reaction of polyurethane acrylate, completing high-hardness surface curing within 2-5 seconds, providing 9H hardness and excellent wear resistance. At the same time, the low sensitivity to oxygen ensures uniform surface curing without adhesion problems. Cationic curing decomposes the thermal cationic initiator at above 110°C, releasing protons to initiate the ring-opening polymerization reaction of epoxy acrylate, forming a deep cross-linked network, effectively reducing the curing shrinkage to less than 2%, significantly reducing internal stress and solving the curling phenomenon, while giving the coating high flexibility and strong impact resistance, and maintaining integrity when the steel ball free fall height reaches 150cm. Through the synergistic effect of rapid surface hardening of free radical curing and deep enhancement of cationic UV curing, the overall performance of the coating is optimized, the transmittance can be stabilized at more than 92%, the optical transparency is excellent and there is no yellowing; the film thickness deviation is controlled within ±0.5μm, and the surface uniformity is high; at the same time, the network structure generated by cationic UV curing has excellent moisture and heat resistance and chemical resistance, suitable for long-term use in harsh environments.

[0111] In summary, the test performance of each embodiment is shown in Table 1:

[0112] Table 1

[0113]

[0114]

[0115] Test description:

[0116] 1. Hardness (H);

[0117] Test method: Use a pencil hardness tester to test. Place the pencil at a 45° angle on the coating surface, apply a certain amount of pressure, scratch the pencil and observe whether there are scratches on the coating.

[0118] Test standard: According to ISO 15184 international standard, the hardness is determined by the pencil model that can pass through but not damage the coating.

[0119] 2. Impact resistance (height of steel ball falling, cm);

[0120] Test method: Use the steel ball free fall method to drop a steel ball of a certain mass from different heights and measure the maximum height at which the coating is not damaged.

[0121] Test standard: According to ASTM D2794 international standard, record the maximum height of the coating without cracking or peeling.

[0122] 3. Bending radius (mm);

[0123] Test method: Use a bending tester to bend the tempered film and measure the minimum bending radius without cracks or delamination.

[0124] Test standard: According to ISO 1519 international standard, record the minimum bending radius.

[0125] 4. Wear resistance (500g pressure, friction times);

[0126] Test method: Use Taber abrasion tester to apply 500g pressure on the coating surface and rub it repeatedly with a friction wheel, and record the maximum number of frictions without penetration of the coating.

[0127] Test standard: According to ASTM D4060 international standard, record the number of frictions.

[0128] 5. Light transmittance (%);

[0129] Test method: Use a spectrophotometer to measure the average transmittance of the coating in the spectral range of 400nm to 700nm.

[0130] Test standard: According to ISO 13468-2 international standard, calculate the ratio of transmitted light to incident light.

[0131] 6. Hydrophobic angle (°);

[0132] Test method: Use a contact angle meter to drop a drop of pure water on the coating surface and measure the contact angle between the water drop and the coating surface.

[0133] Test standard: According to ASTM D7334 international standard, measure three times and take the average value.

[0134] 7. Surface tension (mN / m);

[0135] Test method: Use a contact angle meter to measure the surface tension of the coating surface by the drop method.

[0136] Test standard: According to ASTM D5946 international standard, combined with Young-Laplace formula.

[0137] 8. Film thickness uniformity (deviation, μm);

[0138] Test method: Use a laser film thickness meter to measure the thickness at multiple points on the coating surface and calculate the maximum deviation.

[0139] Test standard: According to ISO 2808 international standard.

[0140] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A free radical-thermal cationic dual-cured tempered film coating, characterized in that: In parts by weight: 0.5-1.5 parts of epoxy acrylate oligomer, 2-4 parts of polyurethane acrylate, 3-6 parts of solvent, 2%-4% of composite photoinitiator accounting for the total weight of the mixture, 0.5%-3% of thermal cationic initiator accounting for the total weight of the mixture, and 1‰-5‰ of auxiliary agent accounting for the total weight of the mixture.

2. The free radical-thermal cationic dual-cured toughened film coating according to claim 1, characterized in that: The composite photoinitiator comprises 1-hydroxycyclohexyl phenyl ketone and 2,4,6-trimethylbenzoyl-diphenyl phosphine oxide, and the ratio of the 1-hydroxycyclohexyl phenyl ketone to the 2,4,6-trimethylbenzoyl-diphenyl phosphine oxide is 2:

1.

3. The free radical-thermal cationic dual-cured toughened film coating according to claim 1, characterized in that: The thermal cationic initiator is diphenyl[4-(phenylthio)phenyl]-sulfonium hexafluoroantimonate.

4. The free radical-thermal cationic dual-cured toughened film coating according to claim 1, characterized in that: The solvent includes butyl acetate, methyl isobutyl ketone and propylene glycol monomethyl ether, and the ratio of the butyl acetate, the methyl isobutyl ketone and the propylene glycol monomethyl ether is 5:3:

2.

5. The free radical-thermal cationic dual-cured toughened film coating according to claim 1, characterized in that: The auxiliary agent is one or more of a leveling agent and a catalyst.

6. A method for preparing a free radical-thermal cationic dual-cured tempered film coating, comprising the free radical-thermal cationic dual-cured tempered film coating of claims 1-5, characterized in that: The steps include: (1) Add 0.5-1.5 parts of epoxy acrylate oligomer, 2-4 parts of polyurethane acrylate and 3-6 parts of solvent into a beaker and stir evenly at room temperature; (2) Then add 2% to 4% of composite initiator, 0.5% to 3% of thermal cationic initiator, and 1‰ to 5‰ of auxiliary agent, and continue to stir evenly; (3) Vacuum degassing and discharging.

7. A method for preparing a free radical-thermal cationic dual-curing tempered film, characterized in that: The steps include: (1) preparing a substrate, uniformly coating a free radical-thermal cationic dual-cured tempered film coating obtained from claim 6 on the surface of the substrate, and baking the coating in an oven at a temperature above 110° C. for 2 min to 4 min; (2) The baked substrate is passed through a high pressure mercury lamp at 600-800 mj / cm 2 Energy curing until the coating is dry; curing time is 1s-5s; (3) The cured substrate is placed in an oven at 60°C-80°C for 24h-48h to complete the preparation.

8. A free radical-thermal cationic dual-cured tempered film, characterized in that: The invention is made based on the method for preparing a free radical-thermal cationic dual-cured tempered film according to claim 7.

9. The free radical-thermal cationic dual-cured tempered film according to claim 7, characterized in that: The substrate is PET.

10. The free radical-thermal cationic dual-cured toughened film coating according to claim 1, characterized in that: The epoxy acrylic oligomer is selected from one or more of Changxing 6270, Changxing 6278, Daicel CELLOXIDE 2000, and Daicel EPOLEAD PB3600.

Citation Information

Patent Citations

  • 3D laser etching light-cured UV coating and preparation method thereof

    CN106752860A

  • LED curing conductive ink for PET film

    CN108610745A

  • Protective film applied to curved display screen

    CN111534244A

  • Preparation method of high-hardness friction-resistant hardened coating

    CN117511385A